2006
DOI: 10.1097/01.tp.0000251718.95622.b3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of FTY720 Versus MMF in De Novo Renal Transplantation

Abstract: While FTY720 2.5 mg plus FDC yielded similar efficacy to MMF plus FDC, the FTY720 5 mg plus RDC did not allow a 50% reduction in cyclosporine exposure. The associated lower creatinine clearance indicated that FTY720 combined with cyclosporine provided no benefit over standard care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 17 publications
(17 reference statements)
1
56
0
1
Order By: Relevance
“…The clinical trials assessing the use of fingolimod as an antirejection agent in renal transplant patients was reported by Salvadori et al 27 and Tedesco-Silva et al 28 Both these clinical trials evaluated higher-dose fingolimod (5 and 2.5 mg) in association with cyclosporine, and both reported higher rates of macular oedema (Salvadori et al: 2.2% at 5 mg dose, 1.3% at 2.5 mg dose), (Tedesco-Silva et al: 3.4% at 5 mg dose and 1.7% at 2.5 mg). Tedesco-Silva and Salvadori did not exclude patients with diabetes in the sample population.…”
Section: Fame and Its Association With Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical trials assessing the use of fingolimod as an antirejection agent in renal transplant patients was reported by Salvadori et al 27 and Tedesco-Silva et al 28 Both these clinical trials evaluated higher-dose fingolimod (5 and 2.5 mg) in association with cyclosporine, and both reported higher rates of macular oedema (Salvadori et al: 2.2% at 5 mg dose, 1.3% at 2.5 mg dose), (Tedesco-Silva et al: 3.4% at 5 mg dose and 1.7% at 2.5 mg). Tedesco-Silva and Salvadori did not exclude patients with diabetes in the sample population.…”
Section: Fame and Its Association With Diabetesmentioning
confidence: 99%
“…25,26 Incidence of FAME Macular oedema has been a well-documented side effect of fingolimod since it was originally evaluated as an anti-rejection agent for renal transplantation. 27,28 Fingolimodassociated macular oedema was therefore monitored for and reported in the initial clinical trials investigating the efficacy of fingolimod for RRMS. The FREEDOMS study was a phase III multicentre, 24-month, double blind randomised study comparing 0.5 mg (n = 425) and 1.25 mg (n = 429) fingolimod daily treatment with placebo (n = 418) in patients with RRMS.…”
Section: Fingolimod and The Eyementioning
confidence: 99%
“…Unexpectedly, both FTY720 treatment arms were associated with lower creatinine clearance and higher incidence of macular edema. 56,57 These results, unexplained but believed to be attributable to nonimmunological renal toxicity, indicated that FTY720 provided no benefit in comparison to standard care and resulted in temporary stopping of the development of FTY720 for renal transplantation.…”
Section: Fingolimod (Fty720)mentioning
confidence: 98%
“…In these studies, fingolimod was associated with the development of macular edema (ME). 4 As a result of this important incidental finding, monitoring of ME was implemented in subsequent trials involving fingolimod in MS.…”
Section: Discussionmentioning
confidence: 99%